The influence of mass and size effects on the radiolysis process of water in the BeO/H₂O suspended system by the γ-quanta - Jafarov, Y.D. (Вопросы атомной науки и техники, 2020)
The amount, formation rate and radiation-chemical yield of molecular hydrogen obtained from water radiolysis process within the system, have been defined according to both water and BeO by maintaining the water volume constant (V = 5 ml); by changing the mass (ᵐBeO= 0.0 (pure water), 0.01; 0.02; 0.04; 0.08; 0.2 g) and particle size (d < 4, d = 32…53 and 75…106 μm) of beryllium oxide in the porous BeO/H₂O suspended systems by the influence of γ–quanta (⁶⁰Co, P = 19.5 rad/s, T = 300 K). It has been established that the amount, formation rate and radiation–chemical yield of molecular hydrogen defined according to both water and BeO from radiation-heterogeneous transformation of water in these systems, change depending on mass and particle size of BeO added to water.